[tex]6\frac{1}{2} = \frac{6\cdot2+1}{2} = \frac{13}{2}\\\\10\frac{1}{4} = \frac{10\cdot4+1}{4} = \frac{41}{4}\\\\3\frac{4}{7} = \frac{3\cdot7+4}{7} = \frac{25}{7}\\\\5\frac{2}{3} = \frac{5\cdot3+2}{3} = \frac{17}{3}\\\\12\frac{2}{3} = \frac{12\cdot3+2}{3} = \frac{38}{3}\\\\6\frac{1}{3} = \frac{6\cdot3+1}{3} = \frac{19}{3}[/tex]
[tex]9\frac{6}{7} = \frac{9\cdot7+6}{7} = \frac{69}{7}\\\\20\frac{1}{4} = \frac{20\cdot4+1}{4} = \frac{81}{4}\\\\5\frac{3}{8} = \frac{5\cdot8+3}{8} = \frac{43}{8}\\\\7\frac{3}{7} = \frac{7\cdot7+3}{7} = \frac{52}{7}[/tex]
[tex]9\frac{4}{9} = \frac{9\cdot9+4}{9} = \frac{85}{9}[/tex]